An Updated Phytopharmacological Review on Medicinal Plant of Arab Region: Apium graveolens Linn - Al‑Asmari, Abdulrahman Khazim; Athar, Md. Tanwir; Kadasah, Saeed G. (Pharmacognosy Reviews)
Apium graveolens Linn. (Karafs) is used in traditional medicine for the treatment of the various ailments. There is a need to explore and authenticate the pharmacological profile and medicinal importance of the Karafs. In this paper, the literature and the published work on Apium were collected using online resources “Google scholar”, “Web of science”, “Scopus” and “PubMed”. Each of the pharmacological activity was searched individually using the keywords “Apium/Karafs/Apium graveolens + individual pharmacological activity”. We documented the most cited and most recent literatures. The current findings illuminate the importance Karafs in the traditional medicine and their impact in treating various diseases. This review strongly supports the fact that the Apium has emerged as a good source of medicine in treating various diseases. There is also a need to isolate the bioactive phytochemicals present in this plant.
Keywords: Apium graveolens; Arab Medicine; Karafs; Traditional Arab and Islamic Medicine